Implementation of green surgery approach in healthcare system and its effect on carbon footprint reduction in operating theatres - Koo, Thai Hau; Leong, Xue Bin; Lee, Yi Lin; Zakaria, Mohd Hazeman; Zakaria, Andee Dzulkarnaen (Penerbit Universiti Sains Malaysia, 2025)
Healthcare systems, particularly operating theatres (OTs), are among the leading causes of pollution due to energy-intensive procedures, anaesthetic gases, and single-use surgical instruments. This perspective review provides actionable, evidence-based recommendations that not only minimise the environmental impact but also offer quality patient care. A wide literature search of available studies on green surgery was conducted. Searches were conducted in databases, including PubMed, Science Direct, Scopus, ProQuest, and Web of Science, from January 2013 to the present. A review of global practices highlighted the effectiveness of green surgical initiatives. Some initiatives related to the health sector report reductions in carbon emissions by reusable surgical instrument implementation in hospitals of up to 97%, energy savings of up to 50% with modifications to heating, ventilation, and air-conditioning (HVAC) systems, and waste management programmes, including the recycling and reprocessing of single-use devices, reporting waste reductions from 40% to 66%. Key strategies include shifting to renewable energy sources by promoting reusable instruments, optimising HVAC systems, and promoting comprehensive staff training for sustainability. All these factors are important for decreasing the environmental burden without compromising operational efficiency. The integration of sustainable practices in Malaysian OTs can significantly reduce carbon emissions and waste generated by hospitals while maintaining patient safety. These measures support the national goals of achieving Sustainable Development Goals (SDGs) and advancing Universal Health Coverage (UHC). Aligning with global sustainability efforts, Malaysia’s health care system can reduce its carbon footprint.